Análise da eficiência de um sistema em escala de bancada para remoção de h2s com soluções contendo íons de ferro - Pirani, Débora Almeida (2016)
In recent decades it has sought new sources of renewable energy. Among the sesources can highlight biogas that comes from anaerobic decomposition of organic matter. Biogas, due to its large amount of methane can be used as a potential source of electrical or thermal energy. In its gaseous composition is present as hydrogen sulfide (H2S), which, despite having a low concentration, it is considered a problem. There are several techniques purifying biogas to remove compounds such as H2Sand CO2. Among the biogas purification techniques are those employing solutions containing iron ions. This work was carried out using solutions containing iron ions to act as removers of biogas hydrogen sulfide. First, the solutions prepared from their on electrolyzing electrodes at two different times, one and three minutes. Subsequently analyzed the iron concentrations in the solutions from the atomic absorption spectrophotometry. The experiments were conducted following a 22factorial design with three central points in a module in bench scale that were varied the ratio L/G (solution flow/biogas flow) and the concentration of iron ions in the solution. The biogas used was from a digester of a swine slaughterhouse. The analysis of the H2S concentration in the purified biogas were performed using a Biofoto (brand Alfakit). According to the test results obtained, a higher removal efficiency was 97.91% under the condition of a concentration of iron ions of1.79 mg.L-1 and L/G of 2.01. Depending on the results obtained, the regression analysis was performed in which it was found that only the concentration of iron ions was significant, ie, an increase at ion concentration increases caused increased removal efficiency. The variable L/G was not significant indicating that the regeneration step in the second column did not work. Thus, one can work on smaller value of L/G which will be obtained the same values of efficiency. After use of the solutions in the system, it is clear that there is a reduction in the concentration of iron in the solutions, proving that the iron ions were consumed in the process.